Goal Commitment as Mediator of Relationship between Emotional Intelligence and Career Decision Difficulties among Vocational High School Students - Zamira, Thalia; Suharso, Puji Lestari (Jurnal Kajian Bimbingan dan Konseling, 2024)
Vocational high school students were provided with a curriculum designed to facilitate their transition into the workforce. Elicitation studies have indicated that vocational high school students experience difficulties in making career decisions. The internship program is designed to enhance students' emotional intelligence and goal commitment, thereby preventing career decision-making difficulties. This research aims to investigate the mediating effect of goal commitment in the relationship between emotional intelligence and career decision-making difficulties. This quantitative correlational research was conducted in a vocational high school in Bogor with a total of 173 participants using a self-report questionnaire of CDDQ, TEIQue-SF, and HWK Scale. Mediation analysis was processed using Hayes PROCESS. Results showed that goal commitment plays a partial mediation role in the relationship between emotional intelligence and career decision-making difficulties (c’ = -0.19, p < 0.001; c = -0.25, p < 0.001). This research will also present the limitations and suggestions for future study.